2000
DOI: 10.1002/qj.49712656404
|View full text |Cite
|
Sign up to set email alerts
|

A gcss model intercomparison for a tropical squall line observed during toga‐coare. I: Cloud‐resolving models

Abstract: Results from eight cloud-resolving models are compared for the first time for the case of an oceanic tropical squall line observed during the Tropical Ocean/Global Atmosphere Coupled Ocean-Atmosphere Response Experiment. There is broad agreement between all the models in describing the overall structure and propagation of the squall line and some quantitative agreement in the evolution of rainfall. There is also a more qualitative agreement between the models in describing the vertical structure of the apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 37 publications
6
60
0
Order By: Relevance
“…Redelsperger et al, 2000), that the use of 2 km horizontal resolution is fine enough to simulate deep convection reasonably well. But, resolution can have a significant effect on convective mixing processes (e.g.…”
Section: Meteorology and Model Initialisationmentioning
confidence: 94%
See 1 more Smart Citation
“…Redelsperger et al, 2000), that the use of 2 km horizontal resolution is fine enough to simulate deep convection reasonably well. But, resolution can have a significant effect on convective mixing processes (e.g.…”
Section: Meteorology and Model Initialisationmentioning
confidence: 94%
“…2-D models have been shown to be able to reasonably simulate some convective systems (e.g. Redelsperger et al, 2000) but have not previously been compared with 3-D models in studies concerning the TTL. It is possible that aspects such as the mixing of the overshoot air with the TTL air and gravity wave production may be wrongly represented by 2-D simulations.…”
Section: -D/2-d Comparisonsmentioning
confidence: 99%
“…In this study, simulations are carried out using cloud-resolving models (CRMs), which explicitly resolve cloud-scale processes, and single-column model (SCM) versions of numerical weather prediction (NWP)/global climate models (GCMs), which parametrize all cloud processes on scales smaller than that of a GCM grid cell (∼ 100 km). Previous model intercomparison studies of deep convective cloud systems using CRMs and SCMs were based upon convectively active periods of field experiments that took place over oceans (Bechtold et al, 2000;Redelsperger et al, 2000) and land (Ghan et al, 2000;Xie et al, 2002;Xu et al, 2002;Guichard et al, 2004;Grabowski et al, 2006). In order to understand the deficiencies in the representations of convective processes in GCMs and, in particular, their ability to simulate tropical variability, the present case study includes both suppressed and active periods of tropical deep convection, as well as the transitions from suppressed to active periods during the suppressed phase of the Madden-Julian oscillation (MJO), which has a period of 40-50 days (Madden and Julian, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…5a). The contrast in mesoscale organization, as well as the differential tilting of cloud structures (Redelsperger et al 2000) would affect the partitioning between convective and stratiform regions, and thus the latent heating profiles. Based on the partitioning technique of Tao et al (1993), the stratiform contribution to the total rainfall in the twodimensional experiment is about 7% greater than in the three-dimensional experiment.…”
Section: Convective Analysesmentioning
confidence: 99%
“…The most pronounced difference is the higher temporal variability of areal average quantities in the two-dimensional configuration, attributed to the smaller number of grid points (Tompkins 2000). In the study of an oceanic tropical squall line, Redelsperger et al (2000) also showed a weak dependency of cloud statistics on dimensionality, but the three-dimensional framework tended to generate less vertically tilting, deeper convective cells and a larger stratiform region. In contrast to the aforementioned short-term simulation studies, Tompkins (2000) examined the effect of dimensionality on radiativeconvective equilibrium statistics, and reported that the two-dimensional configuration gives rise to a warmer and moister boundary layer due to higher surface wind perturbations resulting from convective downdrafts, leading to an apparent warmer moist-adiabatic tropospheric state.…”
Section: Introductionmentioning
confidence: 97%